Health Risk Assessment of Polychlorinated Biphenyls (PCBs) in classroom and office dust samples from Federal University in Abeokuta, Nigeria. - Oluwaseun H, Anselm; Abosede A, Badeji; Aishat, Salaudeen; Iyanuoluwa M, Olagbuyiro; Adejoke D., Osinubi; Hammed O, Ameen (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Polychlorinated biphenyls, also known as PCBs are organochlorine compounds that were commonly applied by industries including agriculture. This study determined the concentrations of 28 PCB congeners in dust samples obtained from offices and classrooms of Federal University of Agriculture in Abeokuta, Nigeria, using gas chromatography-mass spectroscopy (GC-MS). The results revealed that the dust samples collected from the classroom had higher PCB concentrations with a total concentration of 102.02 ng/g and mean concentration of 5.36 ng/g, while dust samples from the offices had a total PCB concentration of 87.22 ng/g with a mean concentration of 3.35 ng/g. For dust samples collected from offices, PCB-52 had the lowest concentration (0.77 ng/g) and PCB-81 had the highest concentration of 8.98 ng/g. For dust samples collected from classrooms, PCB-101 had the lowest concentration of 0.47 ng/g, while the maximum concentration of 23.51 ng/g was noted in PCB-189. The HQ of but samples were >1. Hence, this study suggests that further investigation is needed to determine the variation in concentrations of PCBs in other locations within the school with more focus on specific PCB sources and exposure pathways